Tripled Coincidence Point Theorems for Nonlinear Contractions in Partially Ordered Metric Spaces - Binayak S. Choudhury; Erdal Karapınar; Amaresh Kundu (International Journal of Mathematics and Mathematical Sciences)
Tripled fixed points are extensions of the idea of coupled fixed points introduced in a recent paper by Berinde and Borcut, 2011. Here using a separate methodology we extend this result to a triple coincidence point theorem in partially ordered metric spaces. We have defined several concepts pertaining to our results. The main results have several corollaries and an illustrative example. The example shows that the extension proved here is actual and also the main theorem properly contains all its corollaries.